Preliminary study on Analytical Prediction Model of local impact phenomena on concrete structures against hard missiles - Qadir Bux alias Imran Latif; Ahmad Mujahid, Ahmad Zaidi; Ismail, Abdul Rahman (Universiti Malaysia Pahang (UMP), 2010)
MUCEET 2009 is organized by Malaysian Technical Universities Network (MTUN) comprising of Universiti Malaysia Perlis (UniMAP), Universiti Tun Hussein Onn (UTHM), Universiti Teknikal Melaka (UTeM) and Universiti Malaysia Pahang (UMP), 20th - 22nd June 2009 at M. S. Garden Hotel, Kuantan, Pahang.